Halide-bridged Cu(pyrazine)2 perchlorate layers: Structure and magnetism. (1st October 2019) - Monroe, Jeffrey C.; Landee, Christopher P.; Turnbull, Mark M.; Polson, Matthew; Wikaira, Jan L.
Graphical abstract: In this report a pair of halide-bridged Cu(pyrazine)2 layered complexes with the formula [Cu(pz)2 X]ClO4, where pz = pyrazine and X = Cl (1 ), Br (2 ) are structurally and magnetically evaluated and compared to the complexes [Cu(pz)2 X]BF4 X = Cl (3 ), Br (4 ) described previously by Kubus et al. 2018.1 and2 are isostructural in the space group P 4/ n, a slight reduction in symmetry compared to3 and4 ( P 4/ nbm ), which is considered in terms of magneto-structural comparisons. The magnetic susceptibility of1 and2 were analyzed in terms of the 2D-QHAF model and the Cu-pz-Cu superexchange strength J was quantified (11.20(2) K (1 ) and 11.14(2) K (2 ) at 1 kOe applied field; J  = 11.095(7) K (1 ) J  = 11.29(1) (2 ) at 150 Oe applied field) which are typical of pyrazine bridged Cu(II) complexes. The value of T N is estimated as the temperature at which a kink in the susceptibility occurs (4.2(1) K (1 ), 4.5(1) K (2 )) which was investigated as a field induced spin-flop phase transition via magnetization experiments as a function of field and temperature. The presence of exchange anisotropy is thus considered, and assuming its absence, the interlayer exchange strength J ′ was calculated. Powder EPR spectra of1 and2 revealed axial g -tensors with Lorentzian line shape as expected of exchange coupled systems with a small amount of single-ion anisotropy and fourfold symmetry. Abstract: In this report a pair of halide-bridged Cu(pyrazine)2 layered complexes with the formula [Cu(pz)2 X]ClO4, where pz = pyrazine and X = Cl (1 ), Br (2 ) are structurally and magnetically evaluated and compared to the complexes [Cu(pz)2 X]BF4 X = Cl (3 ), Br (4 ) described previously by Kubus et al. 2018.1 and2 are isostructural in the space group P 4/ n, a slight reduction in symmetry compared to3 and4 ( P 4/ nbm ), which is considered in terms of magneto-structural comparisons. The magnetic susceptibility of1 and2 were analyzed in terms of the 2D-QHAF model and the Cu-pz-Cu superexchange strength J was quantified (11.20(2) K (1 ) and 11.14(2) K (2 ) at 1 kOe applied field; J  = 11.095(7) K (1 ) J  = 11.29(1) (2 ) at 150 Oe applied field) which are typical of pyrazine bridged Cu(II) complexes. The value of T N is estimated as the temperature at which a kink in the susceptibility occurs (4.2(1) K (1 ), 4.5(1) K (2 )) which was investigated as a field induced spin-flop phase transition via magnetization experiments as a function of field and temperature. The presence of exchange anisotropy is thus considered, and assuming its absence, the interlayer exchange strength J ′ was calculated. Powder EPR spectra of1 and2 revealed axial g-tensors with Lorentzian line shape as expected of exchange coupled systems with a small amount of single-ion anisotropy and fourfold symmetry.